Exploring the role of experience, experience intensification on autobiographical memory and nostalgia and behavioural intention - a theory driven approach. (6th December 2021) - Sivakumar, V.J.; Rajadurai, B. Issac Johny
The objective of the research work is analysing post consumption evaluations and influences of experience intensification, memory and nostalgia experience and behavioural intention in theme park research. By the theory driven approach, this study explores the consumers' overall experience and experience intensification on their memory, nostalgia, and behavioural intention. Samples have been collected from 355 theme park visitors from Tamil Nadu. Structural equation modelling and process macros were used for testing the hypothesis. The findings confirmed that the consumers' overall experience positively influences experience intensification; experience intensification has a positive effect on memory and nostalgia; and both consumers overall experience and experience intensification influence behavioural intention. Conclusions of the study provide valuable insights to the practitioners. Suggestions for future research work are also given.